Pengaruh Keragaman Produk, Harga dan Kualitas Produk Terhadap Keputusan Pembelian Konsumen Pada Usaha Pecah Belah Anugrah Bukittinggi - Dian Rahmawaty; Putri, Anne; Nurfitriyenny; Fitria; Supryanita, Rina (Fakultas Ilmu Administrasi Universitas Dr. Soetomo, 2025)
This study investigates the influence of product diversity, pricing, and product quality on consumer purchasing decisions in a traditional household retail context, focusing on Store Pecah Belah Anugrah in Bukit Tinggi, Indonesia. Employing a quantitative descriptive approach, the research utilized primary and secondary data gathered through questionnaires, interviews, and observations from a sample of 100 respondents. Data analysis was conducted using validity and reliability tests, regression model feasibility assessments, descriptive statistics, and binary logistic regression. The findings reveal that both product diversity and product quality exert a significant and positive influence on consumer purchasing decisions, while price demonstrates a negative and statistically insignificant impact. The logistic regression model established that product diversity (Exp(B) = 1.234, p < 0.01) is the most dominant factor influencing consumer choice, indicating that greater product variety enhances the likelihood of purchase by 23.4%. Product quality also showed a significant positive effect (Exp(B) = 1.198, p < 0.05), suggesting that consumers value functional and aesthetic attributes in household goods. Conversely, price (Exp(B) = 0.989, p > 0.05) was not a decisive factor, implying that perceived value, driven by assortment and quality, supersedes price sensitivity in this market segment. The study extends existing consumer behavior theories by affirming that productrelated attributes, especially diversity and quality, are pivotal in traditional retail contexts in developing regions. Practically, the results suggest that retailers should prioritize enhancing product assortments and maintaining quality standards over engaging in price-based competition. These insights have strategic implications for SME retail development and consumer satisfaction in non-metropolitan settings.